Calibration of Waterloss Impacts on Water Distribution and Accessibility in Akure, Nigeria (Global Journal of Science Frontier Research, 2014)
Safe drinking water is a necessity for life. Providing quality drinking water is a critical service that generates revenues for water utilities to sustain their operations. Population growth put an additional strain on the limited resources. The annual volume of water lost is an important indicator of water distribution efficiency, both in individual years, and as a trend over a period of years. Application of deterministic simulation model on public water supply variables reveals the volume of non-revenue water (NRW) and its cost effects have further created a complex system for the availability, distribution and affordability of the utility. Gradual annual increase in public water supply (AWS) from 9.0 *10 6 m 3 to 14.4 * 10 6 m 3 had negative effect on annual water accessed(AWA) with R 2 = 0.096; and highly significant with annual water loss (AWL) with R 2 = 0.99. This development indicates that water loss mainly through leakages and bursts is a function of public water supply. Hence, estimated volume and cost annual revenue water (NRW) in Akure is 6 million m3 and 15.6 million USD respectively. Critical analysis shows that the lost annual revenue could be used to provide education and health services for a period of 6-month in the region.
Keywords: water; NRW; simulation; distribution; resources; public; cost